Low-Voltage Electrical Installations : (IEC, 1998)
The particular requirements of this part of IEC 60364, in association with IEC 60364, parts 1 to 6, apply to the temporary electrical installations in exhibitions, shows and stands (including mobile and portable displays and equipment) to protect users